Phytoestrogen intake and other dietary risk factors for low motile sperm count and poor sperm morphology. (25th July 2020) - Povey, Andy C.; Clyma, Julie‐Ann; McNamee, Roseanne; Moore, Harry D.; Baillie, Helen; Pacey, Allan A.; Cade, Janet E.; Cherry, Nicola M.; ,
Abstract: Background: Few potentially modifiable risk factors of male infertility have been identified, and while different diets and food groups have been associated with male infertility, evidence linking dietary factors including phytoestrogens and semen quality is limited and contradictory. Objectives: To study the associations between phytoestrogen intake and other dietary factors and semen quality. Materials and Methods: A case‐referent study was undertaken of the male partners, of couples attempting conception with unprotected intercourse for 12 months or more without success, recruited from 14 UK assisted reproduction clinics. A total of 1907 participants completed occupational, lifestyle and dietary questionnaires before semen quality (concentration, motility and morphology) were assessed. Food intake was estimated by a 65‐item food frequency questionnaire (FFQ) covering the 12 months prior to recruitment. Analyses of dietary risk factors for low motile sperm concentration (MSC: <4.8 × 10 6 /mL) and poor sperm morphology (PM: <4% normal morphology) used unconditional logistic regression, accounting for clustering of subjects within the clinics, first without, and then with, adjustment for confounders associated with that outcome. Results: High consumption of daidzein (≥13.74 μg/d), a phytoestrogen found in soy products, was a protective factor for MSC with an odds ratio (95%CI) of 0.58 (0.42‐0.82) after adjustment for clustering and potential confounding. Dietary risk factors for PM after similar adjustment showed that drinking whole milk (OR 0.67, 95%CI 0.47‐0.96) and eating red meat were protective with an OR 0.67 (0.46‐0.99) for eating red meat >3 times/wk. Discussion: In this case‐referent study of men attending an infertility clinic for fertility diagnosis, we have identified that low MSC is inversely associated with daidzein intake. In contrast, daidzein intake was not associated with PM but eating red milk and drinking whole milk were protective. Conclusions: Dietary factors associated with semen quality were identified, suggesting that male fertility might be improved by dietary changes.